Hepatic epithelioid hemangioendothelioma, a rare liver tumor: a case report and review of the literature - Deng, Chao; An, Yulong; Liu, Jinli; Wang, Chao; Gou, Haoxian; Zhang, Jinpeng; Gu, Minghui; Li, Mengmeng; Wang, Tao; Luo, Hao (Frontiers in Oncology, 2025)
IntroductionHepatic epithelioid hemangioendothelioma (HEHE) is classified as a rare, low-grade malignant neoplasm of vascular origin. This study presents a case report of a young female patient recently diagnosed with HEHE. A comprehensive review of the current understanding of HEHE is provided, along with the implementation of a novel combination treatment approach based on contemporary knowledge of this rare hepatic malignancy.CaseA 22-year-old female patient, with no prior medical history, underwent a routine health examination five months prior to presentation. Multiple space-occupying lesions in the liver were incidentally detected through ultrasound imaging, despite the patient being asymptomatic. Subsequent positron emission tomography-computed tomography (PET-CT) examination suggested the possibility of benign lesions. Recent follow-up examinations revealed no further progression of the lesions; however, a biopsy of the lesions confirmed the diagnosis of HEHE. Comprehensive imaging studies, including ultrasound, computed tomography (CT), and magnetic resonance imaging (MRI), demonstrated scattered space-occupying lesions throughout the liver, with no evidence of distant metastasis. To minimize surgical trauma and preserve liver function, a multidisciplinary team was consulted, and a treatment plan was devised: liver resection in combination with microwave ablation of the lesions. The patient’s postoperative recovery was uneventful, leading to successful hospital discharge.ConclusionHEHE is characterized by its insidious onset and rarity, often presenting with multiple lesions at the time of clinical diagnosis. While liver transplantation may be considered the optimal treatment for multifocal HEHE, in cases where transplantation is not feasible, the combination of liver resection and microwave ablation of lesions may represent a safe and effective alternative therapeutic approach.